Smoking Habits and Nicotine Dependence Among the General Lebanese Population Before and During Both the Economic Crisis and COVID-19 Pandemic - Nina Rossa Haddad; Charbel B. Aoun; Abdo Mghames; Mustafa Saleh; Mirna N. Chahine (SAGE Publishing, 2024)
Objective Smoking habits have widely changed over time; however, they remain a well-known fashion that risks people's health. In addition, nicotine addiction depends on the interplay between several factors. Our study aimed to understand the smoking habits and nicotine dependence in the Lebanese population before (September 2019) and during (June 2020) the economic crisis and COVID-19 pandemic. Methods This observational cross-sectional survey-based study included 1560 Lebanese individuals aged between 13 and 75 years old from June till October 2020. Data collection was performed through an electronic survey including patients' demographics and validated instruments to assess addiction to nicotine (CAGE, Four C's, Fagerström test, and Smoker's profile scores). Results Out of 1560 participants, 794 (50.9%) were males. The mean age was 26.5 ± 11.69 years, and 67.8% were aged between 18 and 25 years old. We found that 865 (55.4%) participants were smokers. In addition, smoking cigarettes or vaping, significantly increased between September 2019 and June 2020. Our smoker group showed a high CAGE positivity ( P < .001), marked compulsion ( P < .001), and a considerable lack of self-control to surcease smoking ( P < .001). Furthermore, the nicotine dependence score (NDS) increased with age (B = .166) and decreased with higher educational levels (B = −.219). Conclusion During the economic crisis and the COVID-19 pandemic, the Lebanese population showed an increased prevalence of smoking, a high level of CAGE positivity, strong compulsion, and a significant lack of self-control when it came to quitting smoking. This strongly entails public health measures for smoking cessation through national awareness campaigns.